Serum vitamin D receptor and High Mobility Group Box-1 (HMGB1) levels in HIV-infected patients with different immunodeficiency status: A cross-sectional study. (March 2021) - Wardani, Indah Sapta; Hatta, Mochammad; Mubin, Risna Halim; Bukhari, Agussalim; Mulyanto,; Massi, Muhammad Nasrum; Djaharuddin, Irawaty; Bahar, Burhanuddin; Aminuddin,; Wahyuni, Siti
Abstract: Background: HIV-AIDS patients typically have hypovitaminosis D. Vitamin D is a key mediator in inflammatory and infectious diseases, which VDR mediates its biological effect. High-mobility group box 1 protein (HMGB1) modulates HIV-1 replication in vitro. Vitamin D played a role in inhibiting HMGB1 secretion in the animal study. Objectives: This study aimed to examine differences and correlation of vitamin D receptor and HMGB1 protein levels in HIV patients with mild and severe immunodeficiency and healthy control participants. Methods: This study using a cross-sectional design conducted at Volunteer Counseling and Testing (VCT) Clinic in Mataram, West Nusa Tenggara, Indonesia, from January to June 2020. Three groups of study participants were classified as HIV patients with severe immune deficiency (SID), HIV patients with mild immune deficiency (MID), and healthy controls (HC). Results: Mean level of vitamin D receptor in SID HIV group was 25.89 ± 3.95 ng/ml, lower than those in MID-HIV group; 33.72 ± 1.69 ng/ml and in HC group; 50.65 ± 3.64 ng/ml. Mean levels of HMGB1 protein in the SID HIV group were 3119.81 ± 292.38 pg/ml higher than those in the MID HIV group 1553.55 ± 231.08 pg/ml and HC 680.82 ± 365.51 pg/ml. There was a significant and strong negative correlation (r = −0.932) between vitamin D receptor and HMGB1 levels ( p  < 0.01). Conclusions: Strong negative correlation between VDR and HMGB1 in different immunodeficiency statuses suggesting an important role of vitamin D in inflammation control in HIV infection. However, it needs to be confirmed in a further prospective study. Highlights: Study was conducted in developing area in West Nusa Tenggara, Indonesia. This study consists of 3 groups with different immune status. This was the first study that correlates VDR and HMGB1 in HIV-infected patients. Strong correlation suggests association of VDR and HMGB1with HIV infection.